Dampak Model Pembelajaran dan Kebiasaan Membaca Terhadap Kemahiran Menulis Bahasa Inggris (Studi Pada Kelas VIII Semester 1 di MTs Muhammadiyah Curup) - Akmal Fauzan; Bayu Insanistyo (UNIB Press, 2020)
The purpose of the study was to describe the effect of learning models and reading habits on English writing skills in class VIII semester 1 at MTs Muhammadiyah Curup. The method used in this research is quasi-experimental. This study involved 60 students of class VIII MTs Muhammadiyah Curup. The data were obtained with a questionnaire instrument and a test instrument. The results of the test data analysis showed that there were differences in the English writing skills of students who participated in the Moodle-based blended learning model with students who participated in conventional learning models. Then, there are differences in the English writing skills of students who have high reading habits and students who have low reading habits. Furthermore, there is no interaction effect between learning models and reading habits on English writing skills.